Analisis Pengaruh Kendaraan Yang Melakukan Putar Balik Terhadap Kinerja Ruas Jalan (Studi Kasus Pada U–Turn Jl. Bypass Padang) - Aufa Fadhil; Ircham; Veronica Diana Anis (JUSTER : Jurnal Sains dan Terapan, 2024)
Transportation has an important role in human life, because transportation has a big influence on society, economic and social political development of a country. research discusses   analysis of influence of vehicles making a U-turn on Bypass No. KM 15, Aie Pacah, Tangah City, Padang City, West Sumatra. Research purposes is to determine level of service that occurs in traffic flow, to obtain this aim PKJI 2014 is used. This research obtains average travel time for vehicles making a U-Turn, length of queue when making a U-Turn, average travel time average number of vehicles disturbed and not disturbed by U-Turns and knowing level of service on that road section. From data processing it can be concluded that peak hour vehicle speeds are slower than non-peak hour vehicle speeds due to high traffic flow. Meanwhile, waiting time when a vehicle is about to turn around, during peak hours vehicles wait longer than during non-peak hours because volume of vehicles is denser during peak hours. Average queue length in opposite direction during peak hours is longer than during non-peak hours due to the density of vehicles during peak hours, it can be concluded that level of service C.